The Effect of Good Corporate Governance Implementation and Safety Culture on Employee Performance with Job Satisfaction as an Intervening Variable at PT PLN UP3 Lubuk Pakam - Razali Sahlan; Kiki Farida Ferine; Elfitra Desi; Isa Indrawan (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study was designed to investigate how the implementation of Good Corporate Governance (GCG) and a safety culture impacts employee performance, with job satisfaction as an intermediary factor, at PT PLN UP3 Lubuk Pakam. A quantitative survey methodology was employed, involving a total of 101 employees, with census sampling. The data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that both the implementation of Good Corporate Governance (GCG) and a safety culture positively and significantly influence employee job satisfaction. Furthermore, both elements also have a positive and significant influence on employee performance. Job satisfaction significantly improves performance and serves as an effective mediator between Good Corporate Governance (GCG), safety culture, and employee performance. Thus, job satisfaction is crucial as an intermediary factor in improving employee performance. These results are expected to provide valuable advice to management in improving employee performance by strengthening corporate governance and promoting a safety culture.